DOES BRAZIL’S MODEL OF FEDERALISM REQUIRE INSTITUTIONAL REFORM? A DISCUSSION BASED ON THE WILTON PAES DE ALMEIDA’S TRAGEDY - da Costa e Silva Lima, João Marcelo; Joppert Ragazzo, Carlos Emmanuel (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2023)
The political cost-effectiveness of blame-shifting strategies, which produces incentives for low-quality policy responses and creates a democratic accountability problem, becomes particularly apparent in the context of urban tragedies such as the one involving Wilton Paes de Almeida, a low-income residential building in São Paulo owned by the federal government and occupied by a low-income population. We seek to respond to the question of whether Brazil’s model of federalism requires institutional reform in order to address the blame-shifting problem using the Wilton Paes de Almeida tragedy as a case study. First, we ask to what extent can expect blame-shifting strategies to be ultimately corrected by what we call the “regulation” of Brazilian federalism through litigation. Second, we investigate whether institutional reform risks reducing current levels of democratic accountability by altering a desirable institutional framework, where citizens can turn to more than one level of government to address problems. We conclude that the institutional reform of Brazil’s model of federalism should be on the table.